Cognitive‐affective drivers of fixation in threat assessment. (19th October 2020) - Meloy, J. Reid; Rahman, Tahir
Abstract: Pathological fixation – preoccupation with a person or a cause that is accompanied by deterioration in social and occupational functioning – has been found to precede most cases of targeted violence. It is clinically observed and theorized to have three different cognitive‐affective drivers: delusion, obsession, or extreme overvalued belief. Each driver is explained, and case examples are provided in the context of threat assessment. Extreme overvalued belief as a new concept is discussed in detail, both its historical provenance and its demarcation from delusions and obsessions. Threat management for each separate cognitive‐affective driver is briefly summarized, based upon current clinical findings and research. Emphasis is placed upon understanding both the categorical and dimensional nature (intensity) of these cognitive‐affective drivers, and suggested guidelines are offered for the assessment of such in a clinical examination by a forensic psychiatrist or psychologist.